Balanced scorecard as a performance management system in the transformation initiative of two government-linked companies in Malaysia - Abu Bakar, Noor Raudhiah (2017)
Government-linked companies (GLCs) play an important role in the development of the Malaysian economy. To enhance performance in GLCs, Malaysian government introduced GLC Transformation program (GLCT). The first initiative in GLCT is intensifying performance management systems. Most of GLCs claims that they have been adopting Balanced Scorecard (BSC) as a performance management. This study aims to examine the implementation of BSC as a performance management system in two Malaysian GLCs during GLCT programme. The use of BSC as performance management system is by managing the employees performance and controlling employees behaviour different with performance measurement system that only measure the performance. This study integrates Ferreira and Otley’s (2009), and Hopper and Major’s (2007) frameworks for holistic view of implementation of the BSC. The former was adopted to examine the function of BSC as a performance management system in the technical aspects whilst the latter was used to examine the institutionalisation of BSC in both companies. The Hopper and Major’s (2007) frameworks were supplemented by theoretical triangulation involving economic, labour process and actor network theories to enrich the observations and to extend the theory. The underlying institutional theory serves to illuminate the use of BSC as a performance management system in the Malaysian GLCs, and the Hopper and Major’s (2007) framework by combining both new institutional sociology (NIS) and old institutional economy (OIE). This study employed a qualitative, interpretive case-study approach using semi-structured interviews, participant observations and analysis of organisational documents. The interviewees consisted of multi-level of employees across different departments in the two GLCs.The study found that the two GLCs have a good written system of BSC. However, they faced three major issues in implementing the BSC system - (1) ineffectiveness of key performance indicator (KPI) implementation, and the ineffectiveness in the standard settings, accountability, different perception and understanding among the employees; (2) a disputed linkage between BSC and performance evaluations – the employees of both GLCs perceived that performance evaluation is unfair due to moderation practice and the bell curve system; and (3) failure of BSC in controlling the employees’ behaviour. Based on these issues, the implementation of BSC in both GLCs was limited as a performance measurement only. Besides, the BSC system used in both companies did not satisfy the criteria of performance management in terms of standard settings, performance evaluations, and used and control. This study also found that the BSC system implemented in both GLCs has influenced the employees’ behaviour positively and negatively. The BSC system has favourably influenced the employees by encouraging them to become more organised and focused in their work. Nevertheless, the system has undesirably reduced the employees’ motivation, exposed to judgemental bias, and increased interpersonal conflicts among the employees. This study observed that both GLCs adopted the BSC within a complex, interrelated chain of institutions, including the Government, Khazanah Nasional Berhad (Government proxy) as the main shareholder, consultants, employees union and competitor. The adoption and implementation of BSC involve mimetic, coercive and normative pressures as the BSC is seen as a tool to improve competitiveness and efficiency. The implementation of BSC depends on the commitment of all levels of employees including full support from the Chief Executive Officer (CEO) and the top management, full effort from the superiors, and acceptance and understanding from the operational level employees. The study revealed that the BSC was initiated as a rule for the employees to comply and was subsequently viewed as a routine mechanism for appraising the employees’ performances. However, majority of the employees were dissatisfied with the current performance evaluation system. Considering the above findings, this study recommends that an improvement for the performance evaluation is crucial. This can be accomplished by ensuring a comprehensive, fair and mutually acceptable performance evaluation in order to increase the employees’ acceptance. Besides, the superiors should play an important role in controlling the actions of the subordinates and ensuring fair performance appraisals of their subordinates. Next, the superiors need to understand the nature of work assigned to their subordinates, prevent dysfunctional behaviour, provide conducive work environment, and help the employees improve their work performances.